2014
DOI: 10.1016/j.physa.2013.09.059
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing user behavior of the micro-blogging website Sina Weibo during hot social events

Abstract: The spread and resonance of users' opinions on SinaWeibo, the most popular micro-blogging website in China, are tremendously influential, having significantly affected the processes of many real-world hot social events. We select 21 hot events that were widely discussed on SinaWeibo in 2011, and do some statistical analyses. Our main findings are that (i) male users are more likely to be involved, (ii) messages that contain pictures and those posted by verified users are more likely to be reposted, while those… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(60 citation statements)
references
References 21 publications
(12 reference statements)
2
58
0
Order By: Relevance
“…Liu, Liu, and Li (2012) found that source trustworthiness, source expertise, source attractiveness, and the number of multimedia have significant effects on the information retweeting. Guan, Gao, and Yang (2014) found that male users are more likely to be involved in hot events, and messages that contain pictures and those posted by verified users are more likely to be retweet, while those with URLs are less likely. Lun, Peng, Zhang, Wang, and Zhu (2014) found that retweeting and commenting are distinct types of microblogging behaviors.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Liu, Liu, and Li (2012) found that source trustworthiness, source expertise, source attractiveness, and the number of multimedia have significant effects on the information retweeting. Guan, Gao, and Yang (2014) found that male users are more likely to be involved in hot events, and messages that contain pictures and those posted by verified users are more likely to be retweet, while those with URLs are less likely. Lun, Peng, Zhang, Wang, and Zhu (2014) found that retweeting and commenting are distinct types of microblogging behaviors.…”
Section: Literature Reviewmentioning
confidence: 97%
“…The x t in the formulae (2.1) is calculated as: Liu et al (2012) and Guan et al (2014) measure microblog attraction with retweeting times. Lun et al (2014) use numbers of comments to measure microblog attraction.…”
Section: Data Collectionmentioning
confidence: 99%
“…The work [10] is concerned with 21 hot events which were widely discussed on Sina Weibo; it empirically analyzes their posting and reposting characteristics. In the work [2], by automatically identifying events and their associated user-contributed social media documents, the authors show how they can enable event browsing and search in a search engine.…”
Section: Related Workmentioning
confidence: 99%
“…[11] analyzed and compared user behaviors, including textural features, topics and sentiment polarity of micro-posts on two different microblogging platforms: Sina Weibo and Twitter. [12] discussed the posting and reposting characteristics of some hot events. However, so far there exists little knowledge about Chinese tourist's expectations and experiences in Switzerland from Weibo user behavior.…”
Section: User Generated Contentmentioning
confidence: 99%